A prospective cohort study of trends in self‐poisoning, Newcastle, Australia, 1987–2012: plus ça change, plus c'est la même chose. Issue 8 (27th April 2015) - Buckley, Nicholas A; Whyte, Ian M; Dawson, Andrew H; Isbister, Geoffrey K
Abstract: Objective: To examine inhospital mortality and morbidity associated with self‐poisoning with different drug classes over an extended period. Design, setting and participants : A prospective cohort study over 26 years (1987–2012) with limited follow‐up of patients presenting consecutively to a primary and tertiary referral toxicology centre covering Newcastle, Lake Macquarie and Port Stephens, Australia. Main outcome measures: Hospital length of stay, types of drugs ingested, intensive care unit (ICU) admission, requirement for ventilation, inhospital deaths and rates of antidepressant drug use in Australia. Results: Over the study period, there were 17 266 admissions of patients poisoned by 34 342 substances (16 723 drugs available only on prescription). The median length of stay was 16 hours, 12.2% of patients (2101/17 266) were admitted to an ICU, 7.4% (1281/17 266) were ventilated and 78 (0.45%) died in hospital. Patient demographics, social and psychiatric factors remained stable over the 26‐year period, but case fatality decreased (from 0.77% [15/1955] to 0.17% [7/4060]) as did ICU admissions (19.2% [376/1955] to 6.9% [280/4060]), ventilation (13.7% [268/1955] to 4.8% [193/4060]) and LOS. The most frequently ingested substances were alcohol, benzodiazepines, paracetamol, antidepressants and antipsychotics. There was a substantial fall in some highly toxic drugs (tricyclic antidepressants, barbiturates, conventional antipsychotics and theophylline), but increases in less toxic selective serotonin reuptake inhibitors, serotonin–noradrenaline reuptake inhibitors and paracetamol. A greater than sixfold increase in community antidepressant use was accompanied by only minor changes in overall and antidepressant self‐poisoning rates. Conclusion: Over two decades, there were decreases in poisonings by many highly toxic drugs which were associated with substantial reductions in morbidity and inhospital deaths. Despite massive increases in the number of antidepressant prescriptions, neither rates of self‐harm nor the proportion of antidepressant poisonings increased markedly.